Wearable Piezoresistive Sensors with Ultrawide Pressure Range and Circuit Compatibility Based on Conductive-Island-Bridging Nanonetworks - Chan, Hochan; Kim, Sungwoong; Kang, Tae-Hyung; Lee, Seung-Woo; Yang, Gil-Tae; Lee, Ki-Young; Yi, Hyunjung (American Chemical Society, 2019)
Wearable pressure sensors with wide operating pressure ranges and enhanced wearability via seamless integration with circuits can greatly improve the fields of digital healthcare, prosthetic limbs, and human-machine interfaces. Herein, we report an approach based on a conductive-island-bridging nanonetwork to realize wearable resistive pressure sensors that are operative over ultrawide pressure ranges >400 kPa and are circuit-compatible. The sensor has a simple two-layered structure, where nanonetworks of single-walled carbon nanotubes selectively patterned on a surface-modified elastomeric film interface and bridge conductive Au island patterns on printed circuit boards (PCBs). We show that varying the design of the Au islands and the conductivity of the nanonetworks systematically tunes the sensitivity, linearity, and the operation range of the pressure sensor. In addition, introducing microstructured lead contacts into the sensor based on a Au-island-bridging nanonetwork produces a record-high sensitivity of 0.06 kPa(-1) at 400 kPa. Furthermore, the PCB that serves as the bottom layer of the pressure sensor and contains embedded interconnects enables facile integration of the sensor with measurement circuits and wireless communication modules. The developed sensor enables the monitoring of wrist pulse waves. Moreover, an insole-shaped PCB-based pressure-sensing system wirelessly monitors pressure distributions and gait kinetics during walking. Our scheme can be extended to other nanomaterials and flexible PCBs and thus provides a simple yet powerful platform for emerging wearable applications.
Keywords: ELECTRONIC SKIN; MATRIX; ARRAYS